Investigating the influence of language teachers’ constructivist self-efficacy on their practice of constructivism in Ghanaian language and culture instruction - Ernest Nyamekye; Seth Asare-Danso; Emmanuel Amo Ofori (PLoS ONE, 2025)
The education system in Ghana is undergoing a transition from a behaviorist instructional philosophy to a constructivist one, aiming to produce learners who can actively contribute to nation-building. Nonetheless, given the heavy demands on teachers regarding this abrupt shift into constructivist teaching, there is a need to examine teachers’ sense of efficacy in relation to the enactment of the core principles of this novel instructional philosophy—i.e., social, cognitive, and critical constructivism— laid down in the newly introduced standards-based curriculum. An explanatory sequential mixed method was used to obtain data from basic school teachers in the Sunyani-West Municipal of Bono Region, Ghana. Using adapted teacher self-efficacy and constructivist learning environment scales, quantitative data were gathered from 104 teachers. Qualitative data were also gathered from 15 conveniently sampled language teachers to augment the quantitative findings. Using partial least squares structural equation modelling, a significant positive association was discovered between teachers’ efficacy and the practice of social and cognitive constructivism. Nonetheless, teachers’ efficacy did not statistically predict their practice of critical constructivism. The qualitative results showed that sociocultural concerns probably accounted for the insignificant association between efficacy and critical constructivism. It was therefore concluded that sociocultural norms designed for bringing up a child in Ghana tend to inhibit the enactment of critical constructivism. The study recommends that the National Council for Curriculum and Assessment, in partnership with the Ghana Tertiary Education Commission, should update teacher professional development programs in universities and colleges of education to incorporate constructivist principles, particularly critical pedagogy, aiming to produce competent teachers capable of fostering learners’ autonomy, critical thinking, and problem-solving skills as outlined in the Standards-Based Curriculum (SBC).